Characterizations and In Vitro Gut Microbiome Modulatory Effects of Gluco-Oligosaccharides Synthesized by the Acceptor Reactions of Glucansucrase 53 - Bayaman, Rabia Yusra; Alkay, Zuhal; Ispirli, Humeyra; Arioglu-Tuncil, Seda; Dere, Sevda; Can, Hasan; Gonzales, Miguel Angel Alvarez; Sagdic, Osman; Lindemann, Stephen R.; Tuncil, Yunus Emre; Dertli, Enes (MDPI, 2025)
The production of novel oligosaccharides with potential prebiotic effects is of interest to expand the current market and explore the effectiveness of new functional carbohydrate forms. The utilization of glucansucrases is a cost-effective and environmentally friendly biotechnological strategy for producing novel gluco-oligosaccharides through acceptor reactions. In this study, an active glucansucrase (GS53) was used to produce gluco-oligosaccharides via its acceptor reactions with glucose, maltose, and maltotriose, and these oligosaccharides were tested in terms of structure and their gut microbiome modulatory effects. The formations of oligosaccharides were monitored by TLC analysis, and GS53 was active for the three acceptors but not for the other sugars tested. The structural characterization of the gluco-oligosaccharides by 1H NMR analysis revealed the glycosylation of each acceptor with alpha-(1 -> 3) and alpha-(1 -> 6) linkages, whereas LC-MS analysis demonstrated the formations of DP 8, DP 7, and DP 6 oligosaccharides with acceptors maltose, maltotriose, and glucose, respectively. In vitro fecal fermentation analysis, in which microbial short-chain fatty acids (SCFAs) and microbial compositional changes were assessed using gas chromatography and 16S rRNA sequencing, respectively, demonstrated that the gluco-oligosaccharides formed SCFAs-particularly propionate and butyrate-at levels comparable to those observed with inulin, a well-established prebiotic. Additionally, the gluco-oligosaccharides were found to promote the growth of Bifidobacterium adolescentis and Blautia OTUs, which are known to have important physiological functions beneficial to human health. Overall, these results demonstrate that gluco-oligosaccharides synthesized using GS53 through acceptor reactions exhibit prebiotic potentials and could be utilized in the future as dietary supplements as well as in the development of functional foods targeting colonic health.
Keywords: glucansucrases; acceptor reactions; gluco-oligosaccharides; short chain fatty acids; butyrate; propionate; gut microbiome; METABOLISM; SUCCINATE; BACTERIA; Biotechnology & Applied Microbiology; Food Science & Technology